Planning education with self‑organised initiatives: a case study of societal impact using online education - Moreno Pessôa, Igor Tempels (A+BE | Architecture and the Built Environment, 2019)
Massive Open Online Courses (MOOC) are becoming a popular educational tool on different disciplines. Urban planning education is no exception and new MOOCs are being release every year. Nevertheless, it is still not clear how this new learning experience is being developed, delivered and impacting planning education. This article sheds some light on this issue using the case of the Rethink the City MOOC organised by the Faculty of Architecture and the Built Environment of TU Delft. The course received the AESOP Excellence on Teaching award in 2017 and can serve as an example of how planning education is facing these changes. The article briefly introduces the course and develops on the challenges and results of it. Based on the course team experience on preparing and delivering the course, the article aims to contribute to the debate about online education and to support fellow academics involved on the creation of new MOOCs.